Survei Penerapan Model Machine Learning Dalam Bidang Keamanan Informasi - Arif Rachmat (APIC, 2019)
This paper provides a survey that discusses the spread used of machine learning models and algorithm for problems in information security. The breadth of the various types of techniques and methods by machine learning on this survey also figured by given examples of each model in the application for problems related to information security. The results of the study can be concluded that the use of machine learning in information security has spread widely in its use. Some methods are published in standard ways, with expectations this paper will give the insight to develop better models of machine learning applications in information security.